EVALUASI PROGRAM GERAKAN 21 HARI (G21H) CUCI TANGAN PAKAI SABUN TERHADAP PERILAKU CUCI TANGAN SISWA DI SD ISLAM AL-AZHAR 14 SEMARANG - Zidni Nazria; Zahroh Shaluhiyah; Aditya Kusumawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Handwashing with soap among elementary students has not been adapted into a habit. The habit of clean and healthy life based on handwashing with soap practice has to be done for 21 days without breaking through the 21 Day Handwashing With Soap program. Islamic Elementary School Al-Azhar 14 Semarang has implemented G21H CTPS program since 2011 to 2015. Initial survey showed some students were still unable to apply the practice of CTPS after the implementation of G21H CTPS program. The purpose of this study is to analyze the evaluation of G21H CTPS Program on handwashing behavior of students in Al-Azhar Islamic Elementary School 14 Semarang seen from the aspect of input, process, output. This research used both qualitative and quantitative method with indepth interview to G21H CTPS program officer and interview using questioner to student. Subjects in the study consisted of 4 program implementing officers, 3 subjects of triangulation consisted of G21H CTPS Program Coordinator, principal, and guardian. The total population of the study is 160 students, with a sample size of 80 respondents taken using proportional random sampling technique. The result of the research shows that 61,2% respondent have good behavior of CTPS, 53,8% respondent have good process of CTPS, 53,8% respondent have good knowledge about CTPS, and 72,5% respondent stated that facility and infrastructure of CTPS in schools and homes are readily available. The G21H CTPS Program Planning has been well implemented and structured. The implementation of G21H CTPS program has not been running optimally. Supervision, Monitoring, and Evaluation have not run maximally.